Apreciaciones de los docentes frente a los escritos académicos de los estudiantes de la Licenciatura en Educación Básica Primaria (2023)
This article exposes the results of a survey applied to teachers of Bachelor´s Degree in Primary Education, as part of a diagnosis of a research related to the production of academic texts. For the design of the survey, aspects related to evaluation strategies, textual typologies required of students, criteria of academic texts such as: coherence, cohesion, adequacy, ownership and correction were taken into account. This research is mixed, because it involves qualitative and quantitative approaches, techniques and instruments were applied to understand the problem from which this study starts in a broader and clearer way. Once´s the teacher’s responses were analyzed and categorized, it was possible to conclude that the main difficulties that prevail in students when they are writing texts are related to aspects such as: identification of textual typologies, reliable search for information, adequate citation, use of APA rules, vocabulary, among others.